Consideraciones parasitológicas y clínicas sobre 2700 casos de amebiasis intestinal - Greenway, Daniel (1937)
The authors report the experience gathered in more than 2700 Cases of intestinal amebiasis, verified over a total of coprotic (fecal) examinations realized from March 1922 to up to date, which go beyond the limit of 20.000 different pacients. They sustain that there does not exist any healthy amebic « carrier » advising for them the corresponding treatment. They consider amebiasis as a national problem and danger. They find it diffused over all the Country. The authors point out the frequent co-existence of amebiasis with other affections. They indicate the symptomatology emphasizing on the differential diagnosis. Regarding treatment, they consider emetin is the most potent remedy and indispensable in the treatment of amebiasis. They systematically employ emetin hydrochlorid by hypodermic route exclusively, excluding the intravenous and intramuscular method. They have abandoned the use of arsenicals and consider Yatren as coadjuvant to the emetin treatment.